GA Magazine : a monthly gay magazine. (Amsterdam : Jerry Alexanders Group, 1986)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : Nieuwezijds Voorburgwal 14, Amsterdam
Nederlands
Periodiek